2020
DOI: 10.1186/s12943-020-01166-w
|View full text |Cite
|
Sign up to set email alerts
|

mRNA modification orchestrates cancer stem cell fate decisions

Abstract: Despite their small numbers, cancer stem cells play a central role in driving cancer cell growth, chemotherapeutic resistance, and distal metastasis. Previous studies mainly focused on how DNA or histone modification determines cell fate in cancer. However, it is still largely unknown how RNA modifications orchestrate cancer cell fate decisions. More than 170 distinct RNA modifications have been identified in the RNA world, while only a few RNA base modifications have been found in mRNA. Growing evidence indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 122 publications
0
29
0
Order By: Relevance
“…In summary, although RNA m 5 C modification has been known for decades, only recent advances have revealed its important regulatory roles in embryonic development and tumorigenesis (Liang, Lin, Du, Qiu, & Zhang, 2020; Yang, Wang, et al, 2019). It is expected that more detailed mechanisms underlying for m 5 C‐mediated RNA metabolism will be elucidated along with clarification of the whole m 5 C dynamic decoration system, including methyltransferases, demethyltransferases, and reader proteins to further understand its function in RNA processing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, although RNA m 5 C modification has been known for decades, only recent advances have revealed its important regulatory roles in embryonic development and tumorigenesis (Liang, Lin, Du, Qiu, & Zhang, 2020; Yang, Wang, et al, 2019). It is expected that more detailed mechanisms underlying for m 5 C‐mediated RNA metabolism will be elucidated along with clarification of the whole m 5 C dynamic decoration system, including methyltransferases, demethyltransferases, and reader proteins to further understand its function in RNA processing.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a large number of studies have revealed the multiple molecular functions of m 5 C in RNA processing, such as mRNA export (Yang et al, 2017), RNA stability (Chen, Li, et al, 2019; Gigova, Duggimpudi, Pollex, Schaefer, & Koš, 2014; Väre, Eruysal, Narendran, Sarachan, & Agris, 2017; Yang, Wang, et al, 2019), translation (Janin et al, 2019; Tuorto et al, 2012), and long‐distance RNA transport of plant (Yang, Perrera, et al, 2019). Besides, RNA m 5 C modification also plays a vital role in mitochondrial activity (Haag et al, 2016), stress response (Janin et al, 2019; Tang et al, 2020), gametogenesis and embryogenesis (Cui et al, 2017; Hussain, Tuorto, et al, 2013; Yang, Wang, et al, 2019), nerve and brain development (Flores et al, 2017), and multifarious tumorigenesis and migration (Chen, Li, et al, 2019; Liang, Lin, Du, Qiu, & Zhang, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The majority mRNAs with increased or decreased expression were related to hyper m6A methylation. Prior research reports that transcripts with more m6A modifications tend to be less stable and influencing the splicing kinetics of nascent pre-mRNAs (Wang et al, 2014;Louloupi et al, 2018;Liang et al, 2020). However, follow-up studys found that the m6A modificatied mRNA can either promote or inhibit translation, depending on the m6A reading protein "reader" (Leonetti et al, 2020;FIGURE 8 | Co-expression and interaction network analyses between m6A regulators and m6A-RPS.…”
Section: Discussionmentioning
confidence: 99%
“…The use of mitochondrial genes as prognostic factors is likely to apply to CRC patients at all phases, from the early stage to the late stage, to the stage of metastasis. We know that the amounts of mRNA and protein of a gene are associated with many factors, including mRNA modification [ 28 , 29 ], translation efficiency [ 30 , 31 ], and protein stability and degradation [ 32 , 33 ]. A change in the expression of a gene on mRNA may not result in a difference in the protein level that would affect the body's physiological activities.…”
Section: Discussionmentioning
confidence: 99%